2018
DOI: 10.1016/j.alit.2017.04.008
|View full text |Cite
|
Sign up to set email alerts
|

Early control treatment with montelukast in preschool children with asthma: A randomized controlled trial

Abstract: Montelukast is an effective control treatment for preschool children who had asthma symptoms more than once a month but less than once a week.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
1
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 24 publications
0
8
1
2
Order By: Relevance
“…16) However, a recent study compared the efficacy of montelukast maintenance therapy and as-needed β2agonist therapy for 48 weeks in preschool children experiencing asthma symptoms more than once a month but less than once a week. 38) During the study, 28% of the montelukast group and 50% of the no-controller group experienced asthma exacerbations; 21% and 41% of the children, respectively, required increased treatment. Therefore, montelukast use should be considered as maintenance therapy in preschool children with intermittent asthma ( Table 1).…”
Section: Preschool Children With Asthma or Recurrent Wheezingmentioning
confidence: 97%
See 1 more Smart Citation
“…16) However, a recent study compared the efficacy of montelukast maintenance therapy and as-needed β2agonist therapy for 48 weeks in preschool children experiencing asthma symptoms more than once a month but less than once a week. 38) During the study, 28% of the montelukast group and 50% of the no-controller group experienced asthma exacerbations; 21% and 41% of the children, respectively, required increased treatment. Therefore, montelukast use should be considered as maintenance therapy in preschool children with intermittent asthma ( Table 1).…”
Section: Preschool Children With Asthma or Recurrent Wheezingmentioning
confidence: 97%
“…Current clinical practice guidelines recommended controller therapy for children experiencing daytime asthma symptoms more than once a week, with activity limitations, who require the use of a reliever more than once a week, or who have any nighttime symptoms [ 16 ]. However, a recent study compared the efficacy of montelukast maintenance therapy and as-needed β2-agonist therapy for 48 weeks in preschool children experiencing asthma symptoms more than once a month but less than once a week [ 38 ]. During the study, 28% of the montelukast group and 50% of the no-controller group experienced asthma exacerbations; 21% and 41% of the children, respectively, required increased treatment.…”
Section: Clinical Use Of Montelukast In Children With Asthmamentioning
confidence: 99%
“…10 In a study 28% children on montelukast controller therapy had acute exacerbations of asthma. 11 According to a study, combined steroid and montelukast therapy versus only montelukast had same results. 12 In an international study after 8-week treatment, patients who received combined montelukast and inhaled corticosteroid had better outcome in lung function, compared with patients who took only budesonide.…”
Section: Discussionmentioning
confidence: 95%
“…Although studies suggested that montelukast could be used at earlier stages of asthma to prevent disease progression, this drug is not preferred as initial therapy [22]. Together with the direct effects of LTRA, alternative anti-in ammatory and anti-brotic properties of montelukast would be useful in clinical practice.…”
Section: Introductionmentioning
confidence: 99%